PENGARUH PENGETAHUAN KEPEMIMPINAN, LINGKUNGAN KERJA, MOTIVASI KERJA TERHADAP KINERJA KEPALA SEKOLAH DASAR (SD) NEGERI SE-KABUPATEN ROKAN HILIR PROVINSI RIAU - Daim, Zuhri -; Rugaiyah, Rugaiyah; Matin, Matin (JERAM, 2017)
The purpose of this study was to study the effects of leadership knowledge, work environment, work motivation to the performance of principals of Public Elementary Schools in Rokan Hilir Regency of Riau Province. This research uses the quantitative approach with survey method with causal approach and path analysis technique. This study analyzes the influence of one variable on other variables. The variables studied consist of two kinds, namely exogenous variables and endogenous variables. Exogenous variables have an influence on endogenous variables. While endogenous variables can also affect other endogenous variables. The affordable population which is simultaneously the sampling frame is the entire principals who served in Public Elementary Schools at Rokan Hilir Regency as many as 265 schools. The results of this study indicate that: (1) There is a positive direct effect of leadership knowledge on performance, (2) There is a positive direct effect work environment on performance, (3) There is a positive direct effect of work motivation on performance, (4) There is a positive direct effect of leadership knowledge on work motivation, (5) There is a positive direct effect of work environment on work motivation. Thus, the improvement of teachers’ performance can be achieved well if there is a strong effect from the leadership knowledge, work environment, and work motivation that are well built.  Keywords:   leadership knowledge, work environment, work motivation, and performance